THE FORM OF STUDENTS’ POLITENESS IN SRAGEN, JAWA TENGAH - Zahra Fizty Febriadina; Sumarwati Sumarwati; Sumarlam Sumarlam (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2017)
This research is aimed to describe 1) the form of Javanese used in the students’ politeness language on Indonesian lesson at Vocational School; and 2) the  special characteristics of Javanese used in the students’ politeness language on Indonesian lesson at Vocational School. This is descriptive qulitative reseacrh with sociopragmatics approach. The data are the politeness uttarances made by the student which reflect from the form and special characteristics of Javanese in Indonesian language lesson at vocational school. The data are collected by using listening-free-participating-speaking (simak bebas libat cakap/SBLC) technique and data transcription. The data analyzing technique use Miles and Huberman interactive model, that consists of four steps, they are collecting data, reducing data, analizing data and verifying or conclusion drawing by pragmatics comparing methods. The result of the research shows that the form  of politeness using in  Javanese by students are 1) tact maxim; 2) agreement maxim; and 3) the sympathy maxim. The special characteristic of Javanese language uttered by the students are ‘yowis’, ‘rapopo’, ‘genah’ ‘nggih’, ‘apik’, ‘mawon’, ‘mugo’, dan ‘mbah putri’.Keyword: forms of students’ politeness, Vocational School, Javanese LanguageWUJUD KESANTUNAN BERBAHASA SISWA DI SRAGEN, JAWA TENGAHAbstrakPenelitian ini bertujuan untuk mendeskripsikan (1) wujud penggunaan bahasa Jawa dalam kesantunan berbahasa siswa dalam pembelajaran Bahasa Indonesia di Sekolah Menengah Kejuruan; dan (2) kekhasan bahasa Jawa dalam kesantunan berbahasa siswa dalam pembelajaran Bahasa Indonesia di Sekolah Menengah Kejuruan. Metode yang digunakan adalah penelitian deskriptif kualitatif dengan pendekatan sosiopragmatik. Data berupa tuturan siswa yang mencerminkan wujud dan kekhasan bahasa Jawa dalam tuturan kesantunan berbahasa ketika pembelajaran Bahasa Indonesia di SMK. Pengumpulan data menggunakan teknik simak bebas libat cakap (SBLC) dan transkripsi data. Teknik analisis data menggunakan model interaktif Miles dan Huberman yang terdiri dari empat tahap, yaitu pengumpulan data, reduksi data, analisis data, dan verifikasi atau penarikan simpulan dengan metode padan pragmatis. Hasil penelitian ditemukan bentuk bahasa Jawa dalam kesantunan berbahasa siswa terdapat pada (1) maksim kebijaksanaan; (2) maksim kesepakatan; dan (3) maksim kesimpatian. Kekhasan bahasa Jawa yang digunakan dalam tuturan siswa ditandai dengan penggunaan kata ‘yowis’, ‘rapopo’, ‘genah’ ‘nggih’, ‘apik’, ‘mawon’, ‘mugo’, dan ‘mbah putri’.Kata kunci: wujud kesantunan berbahasa siswa, Sekolah Menengah Kejuruan, bahasa Jawa